2014
DOI: 10.1073/pnas.1304988111
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ signaling maintains skin pigmentation homeostasis through regulation of melanosome maturation

Abstract: Cellular homeostasis is an outcome of complex interacting processes with nonlinear feedbacks that can span distinct spatial and temporal dimensions. Skin tanning is one such dynamic response that maintains genome integrity of epidermal cells. Although pathways underlying hyperpigmentation cascade are recognized, negative feedback regulatory loops that can dampen the activated melanogenesis process are not completely understood. In this study, we delineate a regulatory role of IFN-γ in skin pigmentation biology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
107
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(119 citation statements)
references
References 36 publications
(36 reference statements)
9
107
1
2
Order By: Relevance
“…IFN-γ-induced these changes in melanogenesis are reversible. 19) In our study, the results was consistent with the data report, comparing the first column with the second column in Figs. 5A Figs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…IFN-γ-induced these changes in melanogenesis are reversible. 19) In our study, the results was consistent with the data report, comparing the first column with the second column in Figs. 5A Figs.…”
Section: Discussionsupporting
confidence: 93%
“…19) Primary human melanocytes were treated with IFN-γ for 7 d and then allowed to recover for 5 d (day 12) by fresh medium without IFN-γ, the pigmentation process reinitiated. In accordance with those reported in the previous papers, our results also demonstrated that the inhibition of IFN-γ was reversible after the removal of IFN-γ, as shown in the second columns of Figs.…”
Section: Effect Of Cross-talk Between 5-ht and Ifn-γ On Nhem Was Irrementioning
confidence: 99%
“…After parsing the motifs against the known TF binding sites in vertebrates, we compiled lists of top potential TFs binding to each motif (Table S2). We then analysed the expression of six of the TFs, which were predicted by all of the three motif enrichment tools and implicated in pigmentation processes (Barrallo-Gimeno et al, 2004; Cook & Sturm, 2008; Li et al, 2009; Agarwal et al, 2011; Besch & Berking, 2014; Natarajan et al, 2014) (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Natarajan et al indicated a regulatory role of IFN-γ in skin pigmentation. They showed that IFN-γ signaling impedes maturation of the melanosome, which is a major site for synthesis and storage of melanine (7). Altogether, the actual mechanism of melanocytes killing in the skin of patients with vitiligo has not been definitively determined.…”
Section: Dear Editormentioning
confidence: 99%